Risk factor profile for non-communicable diseases: findings of a STEPS survey among the support staff at the University of Pretoria, South Africa - Sithabile Nombulelo Mathunjwa; Tshegofatso Betty Mohlala; Heather Modiehi Legodi (The South African Journal of Clinical Nutrition, 2024)
Background: Non-communicable diseases (NCDs) are an important problem in South Africa; they account for 60% of all deaths. Early screening could help lower NCD incidences and long-term consequences.Objective: The study aimed to profile NCD risk factors among insourced support staff at the University of Pretoria in 2018.Design: A cross-sectional, descriptive study was conducted at the University of Pretoria, Hatfield Campus. The World Health Organization (WHO) STEPwise approach to chronic disease risk factor surveillance (STEPS) questionnaire was administered to collect data in three steps. The participants’ behavioural risk profiles were gathered using the face-to-face interview technique (STEP I), followed by their physical risk profile using anthropometric and blood pressure measurements (STEP II). Last was the biochemical risk profile, including finger-prick blood glucose and cholesterol measurement (STEP III). Data were analysed using Epi-Info, version 3.54.Subjects: A convenient sample of participants aged 18–64 years from the Departments of Industrial Hygiene and Building Services, Landscape Services, Sports Fields Management, and Security Services (n = 146, 60% were females) took part in the study.Results: Most participants (97.8%) had low daily fruit and vegetable intake. Some 80% of the study population always or often added salt to their food when cooking. Daily alcohol consumption was reported by a quarter of the sample. More than two-thirds of all the participants were overweight or obese and 61% had central obesity.Conclusion: The study identified a high prevalence of several NCD risk factors. Tailored nutrition education and monitoring are needed to lower the elevated risk.